Sociodemographic and delivery risk factors for developing postpartum depression in a sample of 3233 mothers from the Czech ELSPAC study - Fiala, Adam; Švancara, Jan; Klánová, Jana; Kašpárek, Tomáš (BMC psychiatry, 2017)
BACKGROUND: In the postpartum period, certain groups of women are at a higher risk for developing depressive episodes. Several studies have described risk factors for developing postpartum depression (PPD). However, these studies have used limited numbers of participants, and therefore the estimated prevalence of PPD varies greatly. METHODS: The objective of this study is to identify the main risk factors for developing PPD by using data collected via the Czech version of the European Longitudinal Study of Pregnancy and Childhood (ELSPAC). This database provides a representative sample (n = 7589) observed prospectively and a large amount of data on depressive symptoms and on biological, socioeconomic, and environmental factors. The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for incidence of PPD. The affective pathology was examined at three time points: before delivery, 6 weeks after delivery, and 6 months after delivery. RESULTS: The prevalence of depressive symptoms before delivery was 12.8%, 6 weeks after delivery 11.8%, and 6 months after delivery 10.1%. The prevalence rates are based on women who completed questionnaires at all three time-points (N = 3233). At all three time points, the main risk factors for developing PPD identified as significant by both univariate and multivariate analysis were personal history of depressive episodes and mothers experiencing psychosocial stressors. Other risk factors occurring in both types of analysis were: family history of depression from expectant mother's paternal side (prenatal), mothers living without partners (6 weeks postpartum) and feelings of unhappiness about being pregnant (6 months postpartum). Several protective factors were also observed: male child gender (prenatal), primiparous mothers (6 months postpartum), and secondary education (prenatal, only by multivariate analysis). Significant risk factors found solely by univariate analysis were family history of depression in both parents of the expectant mother (prenatal and 6 weeks postpartum), family history of depression from subject's maternal side (6 months postpartum), unintentional pregnancy (prenatal and 6 weeks postpartum), feelings of unhappiness about being pregnant (prenatal and 6 weeks postpartum), primary education (prenatal and 6 weeks postpartum), mothers who opted not to breastfeed (6 months postpartum) and mothers living without partners (prenatal and 6 months postpartum). Family savings were identified as protective factor (prenatal and 6 months postpartum). CONCLUSIONS: We identified significant predictors of PPD. These predictors can be easily detected in clinical practice, and systematic screening can lead to identifying potentially at risk mothers. Since the risk is linked with experience of psychosocial stressors it seems that they might benefit from increased psychosocial support to prevent affective pathology.
Keywords: Pregnancy; Humans; zdravotnické přehledy; Longitudinal Studies; ochranné faktory; PPD; socioekonomické faktory; ELSPAC; Female; rizikové faktory; dospělí; Postpartum depression; Protective Factors; lidé; poporodní deprese; Postpartum blues; Socioeconomic Factors; Adult; Depression, Postpartum; ženské pohlaví; longitudinální studie; vedení porodu; Delivery, Obstetric; EPDS; Risk factors; těhotenství; Czech Republic; Cross-Sectional Studies; Mood disorders; Health Surveys; Česká republika; prospektivní studie; průřezové studie; Risk Factors; Prospective Studies